O Serviço Social uruguaio e suas bases críticas - Silva, José Fernando Siqueira Da [UNESP]; Bentura, José Pablo (Cortez Editora Ltda, 2022)
This article aims to discuss the genesis, development and consolidation of the most critical fraction of Social Work in Uruguay. Product of a postdoctoral study conducted at the University of the Republic and funded by Fapesp in 2020, the text addresses the central elements that sustained the formation of a progressive Social Work from the Latin American struggles collectively fought in the 1960s, 1970s and 1980s, and the end of the civic-military dictatorship in Uruguay from 1985.

Este artigo tem por objetivo debater a gênese, o desenvolvimento e a consolidação da fração mais crítica do Serviço Social no Uruguai. Produto de estudo pós-doutoral realizado na Universidade da República e financiado pela Fapesp em 2020, o texto aborda os elementos centrais que sustentaram a formação de um Serviço Social progressista a partir das lutas latino-americanas coletivamente travadas nas décadas de 1960, 1970 e 1980, e o fim da ditadura cívico-militar no Uruguai em 1985.
The Uruguayan Social Work and its critical bases
Keywords: Uruguayan Social Work; Critical Trends; Latin America; Serviço Social Uruguaio; Tendências Críticas; América Latina